NLRP3 inflammasome-driven neurodegeneration and epileptiform activity in a model of epileptogenesis in organotypic slices - Meda, Francisco José Gonçalves (2022)
Tese de mestrado em Biologia Molecular e Genética, Universidade de Lisboa, Faculdade de Ciências, 2021